2022
DOI: 10.1097/bpo.0000000000002273
|View full text |Cite
|
Sign up to set email alerts
|

Displaced Tibia Fractures in Adolescents: Closed Reduction and Casting Versus Flexible Intramedullary Nails

Abstract: Bold values are statistically significant. CRC indicates closed reduction and casting; ESIN, elastic stable intramedullary nail; N, frequency; N%, divided by total in each group (ESIN = 72; CRC = 69); OR, operating room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…While ESIN is becoming a more popular technique with excellent results, complications such as postoperative compartment syndrome, malunion, delayed union, and nonunion have been identified as potential risks of ESIN treatment of pediatric diaphyseal tibial fractures. 3,[5][6][7][8][9][10][11][12][13][14][15] In our series, compartment syndrome occurred in only 4.1% of patients, well below the published rates (8% to 32%). 8,10,16 Open fractures have an increased risk of healing complications, delayed union, nonunion, and residual angular deformity.…”
Section: Discussioncontrasting
confidence: 71%
“…While ESIN is becoming a more popular technique with excellent results, complications such as postoperative compartment syndrome, malunion, delayed union, and nonunion have been identified as potential risks of ESIN treatment of pediatric diaphyseal tibial fractures. 3,[5][6][7][8][9][10][11][12][13][14][15] In our series, compartment syndrome occurred in only 4.1% of patients, well below the published rates (8% to 32%). 8,10,16 Open fractures have an increased risk of healing complications, delayed union, nonunion, and residual angular deformity.…”
Section: Discussioncontrasting
confidence: 71%
“…Previous research on nonoperative treatment for tibial shaft fractures in adolescents demonstrated only a highly variable rate of unplanned surgery-ranging from 4% in Ho et al's study to 40% in Kinney et al's study. 10,11,13 Our comprehensive definition of complications likely contributed to our complication rate being just higher than the rate in Kinney et al's 13 study. While we discuss complications as a single variable, we acknowledge that different complications have unique risk factors.…”
Section: Discussionmentioning
confidence: 73%
“…5 While surgery may be necessary in a subset of adolescents, previous research has suggested that outcomes after cast treatment alone are often favorable with minimal complications. 10,11 This is the largest study to date looking at outcomes after both operative and nonoperative tibial shaft fractures in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…A predictive score was developed to accurately determine infantile Blount disease recurrence after tibial osteotomy and comprises age of <42 months, LaMont classification type C, and medial metaphyseal beak angle of >128°1 9 . Another study of multiple types of coronal plane deformity evaluated the rate of correction for transphyseal screws and growth modulation plates from the time of the surgical procedure to the first postoperative radiograph.…”
Section: Limb Deformity and Reconstructionmentioning
confidence: 99%